EFFICACY OF NARINGIN ON HEPATIC ENZYMES OF CARBOHYDRATE METABOLISM IN STREPTOZOTOCIN - NICOTINAMIDE INDUCED TYPE2 DIABETIC RATS - leelavinothan, pari (International Journal of Pharmaceutical & Biological Archive, 2010)
Dietary antioxidant compounds such as bioflavonoid may offer some protection against the early stage of diabetes mellitus and the development of complications. This study was aimed to evaluate the effect of naringin on blood glucose and glycosylated hemoglobin level; hepatic glucose regulating enzyme activities; glycogen concentration and plasma insulin level in normal and streptozotocin (STZ)-nicotinamide induced diabetic rats. To induce non-insulin dependent diabetes mellitus (NIDDM), single intraperitoneal injection of 65mg/kg STZ, 15 min after the intraperitoneal administration of 110mg/kg of nicotinamide. Diabetic rats were orally administered with naringin (20, 40, and 80 mg/kg body weight) for 6 weeks on glucose and plasma insulin was determined. Administration of naringin at 80 mg/kg significantly decreases blood glucose and increase insulin. Based on these data, the higher dose 80 mg/kg naringin was selected as effective dose for further study. Treatment with naringin resulted in a significant reduction of glycosylated hemoglobin and an increase in total hemoglobin level. Hepatic glucokinase activity and glucose-6- phosphate dehydrogenase were significantly increased whereas the activity of glucose-6-phosphatase and fructose 1,6 bisphosphatase were decreased in diabetic rats administered with naringin. Furthermore, plasma insulin was inversely correlated with the blood glucose level. The current results suggest that naringin can play an important role in preventing the progression of hyperglycemia, partly by increasing hepatic glycolysis and glycogen concentration.